Assessing Student Satisfaction with Selected Schools Services through the 7Ps Marketing Mix: A Study of a Catholic Higher Education Institution in the Philippines - Rosas, Jesa C.; Madrigal, Dennis (Technium Social Sciences Journal, 2024)
Student satisfaction is a crucial indicator of educational quality, extending beyond mere comfort. Hence, this paper examined the college student satisfaction with selected school services at a Catholic institution in Southern Negros Occidental during 2023-2024 in the light of product, price, promotion, place, people, process, and physical evidence relative to sex, academic program, year level, or family income. Likewise, it also investigated the significant difference in their satisfaction when grouped according to the demographics. Using the quantitative design, this was assessed by 328 college students. It employed the modified questionnaire of 7Ps marketing framework which underwent rigorous validation and reliability testing. In data analysis, it utilized mean, standard deviation, Mann Whitney U test, and Kruskal Wallis. This also adhered to the ethical guidelines of the Philippine Health Research Ethics Board. Generally, the students are highly satisfied with the selected school services relative to the 7Ps. In terms of sex, there were significant differences in product, price, promotion, people, and physical evidence. In income, all 7Ps were found to have significant differences. In year level, people and process were found to have significant differences. In academic program, there were significant differences in terms of product, price, promotion, people, process, and physical evidence. Hence, these findings imply the importance of customizing service delivery to meet the unique needs and expectations of diverse student groups. Also, these findings collectively underscore the need for a comprehensive and detailed understanding of student satisfaction, emphasizing the importance of recognizing individual differences and addressing specific concerns to create a more inclusive and supportive learning environment.